88-2h=6h

Simple and best practice solution for 88-2h=6h equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 88-2h=6h equation:



88-2h=6h
We move all terms to the left:
88-2h-(6h)=0
We add all the numbers together, and all the variables
-8h+88=0
We move all terms containing h to the left, all other terms to the right
-8h=-88
h=-88/-8
h=+11

See similar equations:

| 12x+8=6x-8 | | 6(q-)=12q-48 | | 5x+2-4=4(3x-6)-3(x+1)-3 | | 7(a–10)=13–2(2a+3) | | -10(x+2)=64 | | -x=5.5 | | -6/5+1/3y=-3/4 | | 7y-3=3y-2 | | h-78/6=2 | | 3b+2=b-5 | | 10+5m=60 | | N(x)=7 | | 4-9(-2x-3)=-5(-2x+3)-2 | | 0,056*(-108*x+27*x^2+8)=0 | | 4x=7x-36 | | x-0.25x=60 | | x+0.25x=60 | | 8x+3=7(x-1) | | 7+13x=95° | | 3y=53 | | 2(4x+4)=3(2+3x) | | X+1/3x+6=74 | | c-82/2=5 | | Wx5=55 | | 2x+30=75 | | 4n+9-2nn=5 | | 18x+7=11x-1 | | 3=5–2t | | b-29/7=6 | | 6–2v=2 | | w+13=18 | | y/9+31=39 |

Equations solver categories